Multi-array analysis of volcano-seismic signals at Fogo and Brava, Cape Verde - C. Leva; G. Rümpker; I. Wölbern (Solid Earth, 2022)
Seismic arrays provide tools for the localization of events without clear phases or events outside the network, where the station coverage prohibits classical localization techniques. Beam forming allows the determination of the direction (back azimuth) and horizontal (apparent) velocity of an incoming wavefront. Here we combine multiple arrays to retrieve event epicentres from the area of intersecting beams without the need to specify a velocity model. The analysis is performed in the time domain, which allows selecting a relatively narrow time window around the phase of interest while preserving frequency bandwidth. This technique is applied to earthquakes and hybrid events in the region of Fogo and Brava, two islands of the southern chain of the Cape Verde archipelago. The results show that the earthquakes mainly originate near Brava, whereas the hybrid events are located on Fogo. By multiple-event beam stacking we are able to further constrain the epicentral locations of the hybrid events in the northwestern part of the collapse scar of Fogo. In previous studies, these events were attributed to shallow hydrothermal processes. However, we obtain relatively high apparent velocities at the arrays, pointing to either deeper sources or complex ray paths. For a better understanding of possible errors of the multi-array analysis, we also compare slowness values obtained from the array analysis with those derived from earthquake locations from classical (local network) localizations. In general, the results agree well. Nevertheless, some systematic deviations of the array-derived back-azimuth and slowness values occur that can be quantified for certain event locations.